Knowledge, attitude, and reasons for non-uptake of human papilloma virus vaccination among nursing students - Soni Chauhan; Surya Kant Tiwari; Vishal Dubey; Pragya Tripathi; Priyanka Pandey; Anuj Singh; Narendra Pal Singh Choudhary (BMC Medicine)
Abstract Background Cervical cancer is a significant health issue, especially in low- and middle-income countries like India, where it ranks fourth among women. The Human papillomavirus (HPV) vaccination, a vital preventive measure, has suboptimal uptake among nursing students. We aimed to assess the level of knowledge, attitudes, willingness, and reasons for non-uptake of HPV vaccination among nursing students. Methods A descriptive cross-sectional study was conducted from April to June 2023, using a total enumeration method. Data were collected from 313 nursing students using a validated questionnaire covering sociodemographic information, knowledge, attitudes, and reasons for non-uptake of HPV vaccination. Statistical analysis was performed using SPSS version 26.0. Descriptive statistics summarized the data, while binary and multivariable logistic regression analyses identified factors associated with knowledge, attitude, and willingness for HPV vaccination. Results The mean age of the students was 20.98 ± 2.38 years, with the majority being females (81.2%) and unmarried (93.0%). About half of the participants demonstrated moderate knowledge (52.4%) and negative attitudes (50.1%) towards HPV vaccination, with none having received the vaccine. Female students had 4.24 times the odds of having good knowledge (AOR = 4.24, 95% CI = 1.66–10.80), while those pursuing a bachelor’s degree exhibited 2.70 times the odds of good knowledge (AOR = 2.70, 95% CI = 1.40–5.21). In contrast, first-year students had 0.30 times the odds of having good knowledge (AOR = 0.30, 95% CI = 0.11–0.79) but displayed 4.69 times the odds of having a positive attitude (AOR = 4.69, 95% CI = 1.92–11.41). Additionally, Hindu students had 2.44 times the odds of being willing to receive the vaccine (AOR = 2.44, 95% CI = 1.15–5.20). Most participants expressed willingness to receive the vaccine (62.0%), citing reasons such as not being sexually active (35.8%) and needing more information (18.2%) for non-uptake of the vaccine. Conclusions The study highlights gaps in knowledge and negative attitudes towards HPV vaccination among nursing students. Targeted educational interventions and policy initiatives are essential to improve awareness, promote positive attitudes, and increase HPV vaccination uptake among nursing students.